Cultivar improvement and environmental variability in yield removed nitrogen of spring cereals and rapeseed in northern growing conditions according to a long-term dataset - Peltonen-Sainio, Pirjo; Jauhiainen, Lauri (Agricultural and Food Science, 2010)
The balance between applied and harvested nitrogen (yield removed nitrogen, YRN %) is a recognized indicator of the risk of N leaching. In this study we monitored the genetic improvements and environmental variability as well as differences among crop species (spring cereals and rapeseed) in YRN in order to characterize changes that have occurred and environmental constraints associated with reducing N leaching into the environment. MTT long-term multi-location field experiments for spring cereals (Hordeum vulgare L., Avena sativa L. and Triticum aestivum L.), turnip rape (Brassica rapa L.), and oilseed rape (B. napus L.) were conducted in 19882008, covering each crops main production regions. Yield (kg ha-1) was recorded and grain/seed nitrogen content (Ngrain, g kg-1) analyzed. Total yield N (Nyield, kg ha-1) was determined and YRN (%) was calculated as a ratio between applied and harvested N. A mixed model was used to separate genetic and environmental effects. Year and location had marked effects on YRN and Nyield. Average early and/or late season precipitation was often most advantageous for Nyield in cereals, while in dry seasons N uptake is likely restricted and in rainy seasons N leaching is often severe. Elevated temperatures during early and/or late growth phases had more consistent, negative impacts on YRN and/or Nyield for all crops, except oilseed rape. In addition to substantial variability caused by the environment, it was evident that genetic improvements in YRN have taken place. Hence, YRN can be improved by cultivar selection and through favouring crops with high YRN such as oat in crop rotations.;